Respiration rates and its relationship with ETS activity in euphausiids: implications for active flux estimations - Couret, María; Díaz-Pérez, Javier; Sarmiento-Lezcano, Airam N.; Landeira, José María; Hernández-León, Santiago (Frontiers in Marine Science, 2024)
Euphausiids, commonly known as krill, are crucial contributors to the ocean’s active carbon pump, impacting carbon export and sequestration through their diel vertical migration. These organisms feed on organic matter in the epipelagic layer at night and release inorganic carbon in the mesopelagic layer during the day via respiration. Measuring respiration in the mesopelagic layer is challenging due to the difficulties in obtaining direct measurements, as well as the lack of comprehensive data, and reliance on conservative estimates. The measurement of the electron transfer system (ETS) activity is used as a proxy to assess respiration in the mesopelagic layer. However, accurate calibration of respiration rates and ETS activity is imperative through experimental measurements and empirical data. Here, we compared the respiration rates with their respective ETS activities of different species of euphausiids captured at night in the epipelagic layer of the Atlantic Ocean along a latitudinal (42-29°N, 25°W) and a longitudinal (25-13°W, 29°N) transect. Our results revealed a spatial trend in respiration rates, and consequently in ETS activities, with rates decreasing southward and increasing slightly towards the African upwelling region. The Generalized Additive Model (GAM) demonstrated that epipelagic oxygen concentration, chlorophyll a, and the interaction between epipelagic temperature and mesopelagic oxygen concentration significantly influenced euphausiids respiration rates. Furthermore, we observed a strong correlation between respiration and specific ETS activities, with R/ETS ratios exceeding the conservative value of 0.5, which is typically used to estimate respiratory flux.